2004
DOI: 10.1108/14626000410551573
|View full text |Cite
|
Sign up to set email alerts
|

E‐commerce adoption support and advice for UK SMEs

Abstract: The small business sector of the UK economy is extremely important and the government expends considerable resources in providing support services for this sector. This paper investigated the reasons why SMEs move from traditional commerce to e‐commerce, the efficacy of the support services and the barriers encountered by SMEs adopting e‐commerce. The research methodology involved literature review and interviews with SMEs’ owner‐managers and a UK Online business adviser. It was found that at least two “e‐comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 21 publications
6
145
0
5
Order By: Relevance
“…However, others (e.g. Dongen et al, 2002;Simpson & Doherty, 2004) found that a lack of financial resources was not a sufficient factor to set back e-business adoption in small firms. Perhaps due to economic reality, Nigerian small firms lack required financial resources to enable them procure and adopt useful and relevant business tools (Ifinedo, 2005b;.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others (e.g. Dongen et al, 2002;Simpson & Doherty, 2004) found that a lack of financial resources was not a sufficient factor to set back e-business adoption in small firms. Perhaps due to economic reality, Nigerian small firms lack required financial resources to enable them procure and adopt useful and relevant business tools (Ifinedo, 2005b;.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…Similarly, more concerted efforts need to be undertaken to sensitize business owners and their employees or increase awareness of such innovations. The need for e-business payment systems coaching and training is deserving of attention (Simpson & Doherty, 2004).…”
Section: Implication For Research and Practicementioning
confidence: 99%
“…• The extent to which SME owner-managers participate in and get their eBusiness adoption and general business advice via informal, often highly social, business networks (Beckinsale et al, 2006;Gibbs et al, 2007;MacGregor & Vrazalic, 2007;Simmons et al, 2008) and/or get advice from family members (Galloway & Mochrie, 2005;Martin & Matlay, 2003;Simpson & Docherty, 2004;Zheng et al, 2004). This suggests SME owner-managers who are members of personal or business networks might be inclined to follow the advice of opinion leaders in or the norms of these networks concerning blog use.…”
Section: Which Sme Characteristics Are Suited To Blog Use?mentioning
confidence: 99%
“…Other studies have identified enterprise size 4 based on annual turnover (Ramamurthy, et al 1999), while some studies have applied both the number of employees and the revenue as indicators of enterprise size. A wide review of the literature such as Simpson and Docherty (2004), Stockdale and Standing (2006), and Kartiwi and MacGregor (2007) suggests that SMEs have the following characteristics: strong owner influence, centeralised power, lack of specialist staff, small management team, multifunctional management, unwillingness to take risks, low employee turnover, lack of the necessary expertise and avoidance of sophisticated software or IT applications' adoption.…”
Section: Small and Medium Enterprises (Smes)mentioning
confidence: 99%